Tuning protecto‐flexibility in nature: Case of the fish scale. Issue 2 (11th March 2022) - Murcia, Sandra; Ghods, Sean; Ossa, Alex; Arola, Dwayne
Abstract: Fish scales are among the structural materials in nature that are inspiring the design and development of "next‐generation" engineering materials. Fish scales possess a mineralization gradient that divides their thickness into three unique regions, each containing characteristic structures and properties. Here, experiments and complementary numerical modeling are performed to understand the importance of the different geometrical and mechanical parameters affecting the structural behavior of fish scales. Numerical modeling results showed that the stiffness and work to fracture of the scales in flexure are dependent on the amplitude and wavelength of the limiting layer profile. Furthermore, the mechanical response in bending of the scales can be effectively tuned by the suture profile location within the limiting layer thickness. These results highlight the opportunity to tailor the mechanical response of flexible composite laminates through the architecture of the layers and their interfaces to effectively control the protecto‐flexibility. Key Points: This work combines the disciplines of structural biology, materials science and mechanical engineering to identify the key contributions of the microstructure to the inherent protecto‐flexibility of fish scales, a class of natural dermal armor. The interdisciplinary approach enables an identification of how nature adjusts specific morphological parameters to modulate both flexiblity and protection from physical threats. Abstract : Fish scales are among the multi‐functional structural materials in Nature inspiring the design and development of "next‐generation" engineering materials due to their exceptional combination of flexibility and protection. Experiments and numerical modeling help understand the importance of the different geometrical and mechanical parameters affecting the structural behavior of fish scales and how these can be tuned to tailor the mechanical response of advanced protecto‐flexible materials.